Ethical and political dilemmas of local self-government in Poland in the course of systemic transformations (1990–2018) - Kasiński, Michał (Annales. Etyka w Życiu Gospodarczym, 2019)
The study presents critical reflections on the course and results of Polish local self-government reforms from March 1990, when after 40 years of the system of territorial soviets (national councils), self-government was reintroduced into communes, until January 2018, when an attempt to improve the systemic institutions of self-government in communes, poviats and voivodships was once again revisited. The author points out significant discrepancies between the basic ethical and political values of local self-government, i.e. democracy, independence and efficiency, and the changing content of self-government systemic laws as well as the practice of local authorities’ operations, and formulates proposals aimed at repairing Polish local self-government by adjusting its organisation and functioning to the principles resulting from the Constitution of the Republic of Poland and the European Charter of Local Self-Government. He considers as the most important the elimination of pathological phenomena of simulated local democracy which include: a drastically low turnout in elections and referenda, the disappearance of democratic responsibility of local self-government bodies, and the autonomy of the directly elected executive body of the commune from the influence of the local representation. From this point of view, he positively assesses the new regulations, strengthening the guarantee of transparency of operations carried out by local self-government bodies and control rights of councillors, as well as expanding the catalogue of initiative, consultative and control powers of citizens. He points out, however, that ensuring real democracy in of the local authorities requires a deeper reconstruction of the principles of self-government, the election process, and strengthening the role of representation in creating and enforcing the responsibility of executive bodies.